2012
DOI: 10.1002/ijc.27745
|View full text |Cite
|
Sign up to set email alerts
|

Insights into cancer metastasis from a clinicopathologic perspective: Epithelial‐Mesenchymal Transition is not a necessary step

Abstract: Epithelial-mesenchymal transition (EMT) has been implicated as the critical event initiating cancer invasion and metastasis. After disseminating through the circulation, the malignant cells have been proposed to undergo subsequent mesenchymalepithelial transition (MET) to form secondary tumors. However, strong evidence from human tumor specimens for this paradigm is lacking. In carcinomas, cancers derived from epithelial tissues, epithelial morphology and gene expression are always retained to some degree. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 93 publications
3
101
0
3
Order By: Relevance
“…13,14 Histologic grading of most tumors incorporates grade (degree of differentiation), reflected by cell morphology and tissue architecture. 5 Given the high degree of heterogeneity of cell types within tumors and the overall configuration of the tumor microenvironment, cells that are deep within the tumor as opposed to those at the invasive edge may have different gene expression signatures and invasive or metastatic potential; however, it is also possible that single cells or small groups of cells from anywhere in a tumor may …”
Section: Discussionmentioning
confidence: 99%
“…13,14 Histologic grading of most tumors incorporates grade (degree of differentiation), reflected by cell morphology and tissue architecture. 5 Given the high degree of heterogeneity of cell types within tumors and the overall configuration of the tumor microenvironment, cells that are deep within the tumor as opposed to those at the invasive edge may have different gene expression signatures and invasive or metastatic potential; however, it is also possible that single cells or small groups of cells from anywhere in a tumor may …”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, both processes of EMT and MET would be critical for metastasis: EMT for entering dormancy, promoting survival, and drug resistance and MET as the mechanism to reactivate proliferation and self-renewal to initiate metastasis. This could also explain the pathological observation that metastases display epithelial traits rather than mesenchymal characters (Chaffer et al 2007;Korpal et al 2011;Tsai et al 2012;Chui 2013). …”
Section: Exit From Dormancymentioning
confidence: 98%
“…This EMT program in tumor metastasis possesses many morphological and molecular features similar to those of the developmental EMT program. Importantly, due to the heterogeneity and constantly evolving microenvironment in human tumors, the EMT program in metastasis adapts to these conditions to allow tumor cells to successfully metastasize.While EMT has been accepted as a critical program during embryogenesis, its role in carcinoma metastasis has been under debate (Tarin et al 2005;Thomson et al 2005;Garber 2008;Ledford 2011;Chui 2013). Many cell culture and mouse tumor model studies have clearly demonstrated the importance of EMT in tumor progression.…”
mentioning
confidence: 99%
“…While EMT has been accepted as a critical program during embryogenesis, its role in carcinoma metastasis has been under debate (Tarin et al 2005;Thomson et al 2005;Garber 2008;Ledford 2011;Chui 2013). Many cell culture and mouse tumor model studies have clearly demonstrated the importance of EMT in tumor progression.…”
mentioning
confidence: 99%